Legal Status of IPEDA and Letter C in Land Ownership Proof: Status Hukum IPEDA dan Surat C dalam Bukti Kepemilikan Tanah - Ainul Rifdatul Khoirot; Sri Budi Purwaningsih (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Land administration in Indonesia involves diverse documentary evidence, particularly for uncertified land where formal titles are absent. Specific Background: Among commonly used administrative documents are IPEDA (Regional Development Contribution) records and Letter C village registers, both historically employed to document land control and fiscal obligations. Knowledge Gap: Despite frequent use in disputes, the comparative legal standing and evidentiary role of these two documents within the national land law framework remain insufficiently clarified. Aims: This study analyzes the juridical proof value of IPEDA and Letter C as evidence of land ownership in Indonesian land disputes. Results: Using a normative legal method with statutory, historical, and case approaches, the study finds that neither document constitutes formal proof of ownership under the national land registration system; however, both possess significant administrative and historical evidentiary value. Letter C records local land control and ownership history at the village level, while IPEDA demonstrates a fiscal legal relationship between individuals and the state regarding land utilization. When supported by continuous, legitimate, and undisputed possession, these documents may serve as initial evidence in first land registration or dispute resolution. Novelty: The research provides a comparative juridical evaluation of two non-certificate documents simultaneously, highlighting their complementary roles in evidentiary practice. Implications: The findings underscore the continued legal relevance of traditional administrative records as a bridge between customary land tenure and the formal modern land system, particularly amid ongoing digital transformation of land administration. Highlights: Village land registers document hereditary control history at the local level. Fiscal payment records indicate a state–individual legal relationship over land use. Both documents function as preliminary proof in registration or dispute processes when supported by continuous possession. Keywords:IPEDA; Letter C; Land Ownership Proof; Administrative Evidence; Land Dispute